THE DISSOCIATION OF CARBONIC ACID IN NaCl SOLUTIONS AS A FUNCTION OF CONCENTRATION AND TEMPERATURE - Millero F.; Huang F.; Graham T.; Pierrot D. (My University, 2007)
Potentiometric measurements of the stoichiometric constants for the dissociation of carbonic acid in NaCl solutions (K1∗=[H+][HCO3-]/[CO2] and K1∗=[H+][CO32-]/[HCO3-]) have been made as a function of molality (0–6m) and temperature (0–50°C). The results have been fitted to the equationspKi∗-pKi=Ai+Bi/T+CilnTThe values of pKi in pure water are taken from the literature and the adjustable parameters Ai, Bi and Ci are a function of molalityA1=35.2911m0.5+0.8491m-0.32m1.5+0.055m2B1=-1583.09m0.5C1=-5.4366m0.5A2=38.2746m0.5+1.6057m-0.647m1.5+0.113m2B2=-1738.16m0.5C2=-6.0346m0.5(σ=0.013 for pK1∗ and σ=0.020 for pK2∗, N=603). The values determined in this study are in good agreement with the 25°C literature values. Our results have been combined with previous measurements to derive equations that are valid from 0 to 250°C and 0 to 5m. This large data set has been used to determine the Pitzer parameters (β(0), β(1) and Cϕ) for the interactions of Na+ with HCO3− and CO32− from 0 to 250°C. These results extend the carbonate system Pitzer model to hydrothermal brines containing high concentrations of NaCl.
Keywords: BRINE; CARBON; CONCENTRATION (COMPOSITION); DATA SET; DISSOLUTION; HYDROTHERMAL SYSTEM; SODIUM CHLORIDE; STOICHIOMETRY; TEMPERATURE EFFECT